Sustaining cocoa production on oxisols in Malaysia - Jusop, Shamsuddin; Panhwar, Qurban Ali; Ismail, Roslan; Che Ishak, Fauziah; Naher, Umme Aminun; Hakeem, Khalid Rehman (Springer International Publishing, 2015)
Oxisols are dominated by variable charge minerals in their clay fraction, containing an insufficient amount of Ca and Mg in their soil solutions. Under natural conditions, cocoa grown on the soils is subjected to the stress of low pH and Al and/or Mn toxicity, which eventually produces low yields. This chapter discusses the chemical properties of Oxisols in Malaysia and explains how the productivity of the soils is enhanced using lime or basalt, which increases soil pH. When the pH goes up above 5, Al in the soil solutions is precipitated as inert Al-hydroxides, with the concomitant elimination of toxic Mn. The increase in pH would result in the increase of the CEC, attributed to the reaction of the variable charge minerals present in the soils. Basalt application would also lower pH of the soils, which further increases the CEC. On dissolution, lime supplies Ca and Mg into the soils, and basalt not only releases these metals, but also K, P, and S. Ca, by itself, is able to reduce Al toxicity. One of the best methods of alleviating the infertility of Oxisols for cocoa cultivation is to apply basalt in combination with organic materials. Growing cocoa on Oxisols requires heavy application of NPK fertilizers, usually in the form of ammonium sulfate, rock phosphate, and muriate of potash, respectively. Occasionally, kieserite is applied to increase Mg reserve in the soils. Application of a high amount of N fertilizer will in the end acidify the soils, but it will be offset by the production of hydroxyl ions due to the specific adsorption of phosphate and sulfate ions on the surfaces of the oxides of Fe present in the soils. In that way, the production of cocoa on the Oxisols of Malaysia is sustained.